Reconceptualizing Sharia Philosophy: Aligning Divine Legal Principles With Modern Legal Realities - Mohammad Syafa'ad; Achmad Musyahid; Lomba Sultan (Faculty of Law, Muhammadiyah University of Surabaya, 2025)
The development of modern society presents new challenges in understanding and implementing Islamic law, particularly in maintaining the relevance of divine values within Sharia in response to contemporary needs. The legal issue addressed in this study concerns the position and scope of the philosophy of Sharia in bridging transcendental Islamic legal norms with continuously evolving social dynamics. This research aims to analyze the concept of Sharia philosophy as an epistemological and normative foundation for the development of adaptive Islamic law without abandoning its essential principles. The method employed is normative legal research using conceptual and philosophical approaches through an extensive literature review of classical and contemporary works on Sharia and Islamic legal philosophy. The findings reveal that the philosophy of Sharia does not merely focus on ritual worship (ibadah) and social transactions (muamalah), but also encompasses rational, ethical, and teleological dimensions of Islamic law, which are reflected in four principal domains: Asrar al-Ahkam (the secrets of Islamic law), Khashaish al-Ahkam (the distinctive features of Islamic law), Thawabi’ al-Ahkam (the characteristics of Islamic law), and Mahasin al-Ahkam (the virtues of Islamic law). These four dimensions affirm that the philosophy of Sharia functions as an intellectual framework for interpreting the objectives, values, and contemporary relevance of Islamic law in a proportional and just manner.